Role of CD34 in inflammatory bowel disease - Li, Zhiyuan; Dong, Shuyan; Huang, Shichen; Sun, Yuhan; Sun, Yingzhi; Zhao, Beibei; Qi, Qiulan; Xiong, Lei; Hong, Feng; Jiang, Yuxin (Frontiers in Physiology, 2023)
Inflammatory bowel disease (IBD) is caused by a variety of pathogenic factors, including chronic recurrent inflammation of the ileum, rectum, and colon. Immune cells and adhesion molecules play an important role in the course of the disease, which is actually an autoimmune disease. During IBD, CD34 is involved in mediating the migration of a variety of immune cells (neutrophils, eosinophils, and mast cells) to the inflammatory site, and its interaction with various adhesion molecules is involved in the occurrence and development of IBD. Although the function of CD34 as a partial cell marker is well known, little is known on its role in IBD. Therefore, this article describes the structure and biological function of CD34, as well as on its potential mechanism in the development of IBD.